Security Evaluation of Open Access Wi-Fi Networks in a Public University in Junin, Peru - Aguilar Solis, Brayan Marlon (2024)
This article develops a topic of interest for users who can access the Internet and do not know the dangers of connecting to a free access network where the administrator of this is unknown, so a connection to this network would not be recommended. The central theme of this research is to demonstrate the risks of connecting to unknown access networks. The methodology used was the evaluation of how many users were being connected to the network created to monitor. The data obtained from users already connected have also been evaluated. According to the days they were connected through the networks, there is a strong demand for connected users. The conclusions show that some users are unaware of the dangers of connecting to one of these networks mentioned above and the risk of the amount of information that a person connected to the same network can obtain with the help of programs already created for its correct use. This work is a product of evaluating the dangers of connecting to an unknown network in Huancayo, Peru.